2020
DOI: 10.1021/acs.langmuir.0c01130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cationic Brush-Type Copolymers on the Colloidal Stability of GdPO4 Particles with Different Morphologies in Biological Aqueous Media

Abstract: In this study, we present the synthesis of cationic brush-type polyelectrolytes and their use in the stabilization of GdPO 4 particles in aqueous media. Polymers of various compositions were synthesized via the RAFT polymerization route. SEC equipped with triple detection (RI, DP, RALS, and LALS) was used to determine the molecular parameters ( M n , M w , M w / M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It is well established that if the absolute of zeta potential (ζ) determined for colloid systems exceeds ±25 mV, the electrostatic repulsion forces overdominate the forces caused by van der Waals and could ensure efficient colloidal stability. , To evaluate the colloidal stability of ligand-free UCNPs in water, the zeta potential as a function of pH was measured, and the obtained results are presented in Figure a. We want to emphasize that the zeta potentials of all UCNPs were similar, regardless of their chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that if the absolute of zeta potential (ζ) determined for colloid systems exceeds ±25 mV, the electrostatic repulsion forces overdominate the forces caused by van der Waals and could ensure efficient colloidal stability. , To evaluate the colloidal stability of ligand-free UCNPs in water, the zeta potential as a function of pH was measured, and the obtained results are presented in Figure a. We want to emphasize that the zeta potentials of all UCNPs were similar, regardless of their chemical composition.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the spectrum of SS2 does not show these components, owing to its high temperature synthesis. It is worth noting that a poorly hydrophilic surface is indicative of low colloidal stability in aqueous media 47 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, suspensions with low zeta potentials tend to aggregate or agglomerate. Here, the agglomerates sized around 600 nm over time correlate with the low zeta potential, near isoelectric point, a feature of colloids that trend to agglomerate (Klimkevicius et al, 2020). In addition, the polydispersity index confirmed that the suspension was heterogeneous meaning that E171 agglomerates displayed different sizes.…”
Section: Discussionmentioning
confidence: 99%